2022
DOI: 10.1177/02646196211067358
|View full text |Cite
|
Sign up to set email alerts
|

A survey of mobile app use among university students with visual impairment in India

Abstract: Mobile phones/devices are an important part of our daily lives for sighted people and those with visual impairment (VI) in India. This study explores how Indian university students use and perceive mobile apps and identify the challenges in their usage. A paper-based survey was administered for 124 college students who were legally blind. The survey had items relating to sociodemographic information, use of mobile devices and apps, and the use of apps specifically designed for persons with VI. Results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
(25 reference statements)
0
3
0
1
Order By: Relevance
“…Facebook, Instagram and YouTube, and video-based communication; Skype and WhatsApp. A recent survey involving visually impaired Indian university students revealed that WhatsApp is highly popular among them (Pandey, Lee, Banda, Griffin-Shirley, Nguyen, & Othuon, 2023). This is primarily attributed to its user-friendly interface and accessibility features (Pandey et al, 2023;Ranjan, Gupta, Kapoor, & Bansal, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facebook, Instagram and YouTube, and video-based communication; Skype and WhatsApp. A recent survey involving visually impaired Indian university students revealed that WhatsApp is highly popular among them (Pandey, Lee, Banda, Griffin-Shirley, Nguyen, & Othuon, 2023). This is primarily attributed to its user-friendly interface and accessibility features (Pandey et al, 2023;Ranjan, Gupta, Kapoor, & Bansal, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey involving visually impaired Indian university students revealed that WhatsApp is highly popular among them (Pandey, Lee, Banda, Griffin-Shirley, Nguyen, & Othuon, 2023). This is primarily attributed to its user-friendly interface and accessibility features (Pandey et al, 2023;Ranjan, Gupta, Kapoor, & Bansal, 2023). Moreover, students frequently employ WhatsApp for various purposes, such as communication, sharing academic updates, and exchanging coursework (Ghandour, Woodford, Almutairi, & Al-Srehan, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…There have been a lot of discussions recently about the use of mobile technology in education, including studies on the effects of distractions on task performance (Hsu et al, 2021) and the provision of course and exam information (OConnor & Stricklan, 2021), as well as studies on how to engage math students in a class (Attard, 2018). (Pandey et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Alguns trabalhos (ACOSTA-VARGAS et al, 2020; indicam a existência de problemas recorrentes, independente do tipo de aplicativo. Com o objetivo de superar essas barreiras, pesquisas têm explorado requisitos específicos para aplicativos móveis voltados para pessoas com deficiência visual (SIEBRA et al, 2016;PANDEY et al, 2022;BALLANTYNE et al, 2018).…”
Section: Recomendações De Acessibilidade Para Usuários Com Deficiênci...unclassified